Peran Lembaga Non-Pemerintah dalam Perlindungan Hak Ulayat Masyarakat Adat terhadap Ekspansi Perkebunan Sawit - Salma Inayah Novialita Boru Tambunan; Marselino Bensananda Ernanto; Annabel Shelomita; Aprila Niravita (Jurnal Hukum dan Sosial Politik, 2024)
Agrarian conflicts related to customary land rights in Indonesia, particularly due to the expansion of oil palm plantations, have become a complex issue that has had a major impact on the social, cultural, and economic lives of indigenous communities. Land conversion carried out without adequate consent from indigenous communities often results in unilateral land acquisition, which triggers prolonged conflict. This article discusses the strategic role of non-governmental organizations (NGOs) in protecting indigenous peoples' rights through legal assistance, policy advocacy, and mediation. NGOs play a role in strengthening the legal position of indigenous communities, raising awareness of their rights, and bridging communication between indigenous communities, the government, and companies. However, this role faces challenges in the form of limited authority, external pressure, and overlapping agrarian regulations. This article emphasizes the importance of recognizing indigenous peoples' rights, improving regulations, and an inclusive conflict resolution approach so that economic development can proceed without sacrificing the sustainability of indigenous peoples' lives and cultures.